1990
DOI: 10.1111/j.1471-0528.1990.tb02445.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of ectopic pregnancy by vaginal ultrasonography in combination with a discriminatory serum hCG level of 1000 IU/1 (IRP)

Abstract: The diagnostic value of vaginal sonography in combination with a discriminatory serum hCG level of 1000 iu/l (International Refercnce Prcparation) was tcsted prospectively in 200 pregnant women suspected of having an cctopic pregnancy. An ectopic pregnancy was diagnosed in 68 women (34%,), a miscarriage in 56 (28%) and a normal pregnancy in 76 (38%). On admission, an intrauterinc sac was sccn in 89% of the intrauterinc pregnancies, but in none of the ectopic prcgnancics. Dctection of an adnexal mass separate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
2
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(109 citation statements)
references
References 12 publications
3
100
2
4
Order By: Relevance
“…It is assumed that some miscarriages are due to a primary failure of the trophoblast to produce hCG. Low levels of hCG in the first trimester of pregnancy has long been considered as a predictor of miscarriage, ectopic pregnancy, and failure of IVF procedure [7][8][9]. Intensive studies have revealed that its function includes maintaining the production of steroid hormones and other growth factors in the corpus luteum, blastocyst implantation, uterine vascularization and angiogenesis, uterine quiescence, and immunological adaptation during pregnancy [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that some miscarriages are due to a primary failure of the trophoblast to produce hCG. Low levels of hCG in the first trimester of pregnancy has long been considered as a predictor of miscarriage, ectopic pregnancy, and failure of IVF procedure [7][8][9]. Intensive studies have revealed that its function includes maintaining the production of steroid hormones and other growth factors in the corpus luteum, blastocyst implantation, uterine vascularization and angiogenesis, uterine quiescence, and immunological adaptation during pregnancy [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…CGB genes encode the receptor-binding and hormonespecific subunit of human chorionic gonadotrophin (hCG), which is an indispensable placental hormone in human pregnancy [6]. Low levels of hCG during the first trimester of pregnancy are related to miscarriage and ectopic pregnancy [7][8][9]. At the same time, high concentration of hCG, especially its beta subunit, is a diagnostic marker for gestational trophoblastic diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice the vast majority of ectopic pregnancies can be visualised using TVS [3,4]. Consequently, the use of laparoscopy as a tool to diagnose ectopic pregnancy should be the exception rather than the rule.…”
Section: Surgical Management Of Tubal Ectopic Pregnancymentioning
confidence: 99%
“…If a pregnancy cannot be seen using TVS, then it is classified as a pregnancy of unknown location (PUL), 10% of which are ectopic pregnancies. One should visualise between 87 and 93% of ectopic pregnancies using TVS prior to surgery [3,4]. Misdiagnosis should be a rare event with the use of TVS.…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic pregnancy is a tragedy of reproduction, and a form of reproductive failure in index pregnancy of effected women. Such women have a 7-15% chance of recurrence, and only 40-60% chance of conceiving after surgery [14]. Ectopic pregnancy presents a major health problem for women of childbearing age, and if not treated vigorously and early enough it may be fatal and is of immerse concern to reproductive health and is associated with significant maternal morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%